Management of hazardous waste and contaminated land - Hilary Sigman; Sarah Stafford (Rutgers University, Department of Economics, 2010)
Regulation of hazardous waste and cleanup of contaminated sites are two major components of modern public policy for environmental protection. We review the literature on these related areas, with emphasis on empirical analyses. Researchers have identified many behavioral responses to regulation of hazardous waste, including changes in the location of economic activity. However, the drivers behind compliance with these costly regulations remain a puzzle, as most research suggests a limited role for conventional enforcement. Increasingly sophisticated research examines the benefits of cleanup of contaminated sites, yet controversy remains about whether the benefits of cleanup in the U.S. exceed its costs. Finally, research focusing on the imposition of legal liability for damages from hazardous waste finds advantages and disadvantages of the U.S. reliance on legal liability to pay for cleanup, as opposed to the government-financed approaches more common in Europe.
Keywords: Q5; 330; environmental economics; pollution; liability; enforcement; superfund; Sonderabfall; Bodensanierung; Abfallentsorgung; Bodenschutz; Rechtsdurchsetzung; USA